Relationship between IFNA1, IFNA5, IFNA10, and IFNA17 gene polymorphisms and Crimean‐Congo hemorrhagic fever prognosis in a Turkish population range. Issue 7 (6th January 2016) - Elaldi, Nazif; Yilmaz, Meral; Bagci, Binnur; Yelkovan, Izzet; Bagci, Gokhan; Gozel, Mustafa Gokhan; Engin, Aynur; Bakir, Mehmet; Dokmetas, Ilyas
Abstract : Crimean‐Congo hemorrhagic fever (CCHF) is a fatal emerging acute viral infection. Not much is known regarding the pathogenic mechanisms and the reasons behind severe or mild disease courses in CCHF. IFN‐alpha (IFNA) is one of the essential cytokines in the immune system. Existence of single nucleotide gene polymorphisms (SNPs) in cytokines can cause susceptibility or resistance to viral agents and different clinical courses. Hence, the relationship between SNPs in genes encoding cytokines ( IFNA1 ‐1823G/A (rs1332190), IFNA5 ‐2529T/A (rs758236), IFNA10 Cys20stop (rs10119910), and IFNA17 Ile184Arg (rs9298814) SNPs and disease susceptibility were investigated. The associations between SNPs and CCHF prognosis were also studied. Total 150 patients with CCHF and 170 healthy individuals were enrolled. Genotyping was performed by PCR‐RFLP methods. The frequency of IFNA1 ‐1823 (rs1332190) GG genotype was significantly higher in control subjects than CCHF patients (20% vs. 8%; P  = 0.01). For IFNA17 Ile184Arg (rs9298814) polymorphism, CCHF patients having TG genotype had a higher frequency than the control subjects (38% vs. 32.4%; P  = 0.039). The distribution of TT + TG genotype frequencies was also significantly higher in CCHF group than the controls (97.3% vs. 91.8%; P  = 0.049). Genotype and allele frequencies for IFNA subtypes between fatal and survivors were the same ( P  > 0.05). Genotype and allele frequencies between severe and mild/moderate CCHF patients were also the same ( P  > 0.05). The results show that IFNA1 rs1332190 and IFNA17 rs9298814 SNPs may play an important role in CCHF susceptibility. Determining the existence of other connections for IFNA SNPs and CCHF severity and fatality requires further investigations. J. Med. Virol. 88:1159–1167, 2016 . © 2015 Wiley Periodicals, Inc.